2019
DOI: 10.1007/s13361-019-02269-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Polymer-Coated Probe Electrospray Ionization Mass Spectrometry Determines Phorbol Esters and Deoxyphorbol Metabolites in Jatropha curcas Leaves

Abstract: In this study, a molecularly imprinted polymer-coated probe electrospray ionization mass spectrometry (MIPCPESI-MS) method was developed for detection of phorbol esters (PEs) and deoxyphorbol metabolites in Jatropha curcas leaves. Such an approach was established by sticking on a metallic needle a molecularly imprinted polymer to particularly design a MIP-coated probe for selective sampling and ioni zation of PEs and deoxyphorbol metabolites. By a subsequent application of a high voltage and methanol, as spray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…In addition, the intraday accuracy ranged from −2.1 to −5.1% and the interday from 0.5 to 8.9%. These results are consistent with previous reports using LC–MS , and ambient MS approaches , in which the accuracy and precision variations are expected to be below 20%.…”
Section: Resultssupporting
confidence: 93%
“…In addition, the intraday accuracy ranged from −2.1 to −5.1% and the interday from 0.5 to 8.9%. These results are consistent with previous reports using LC–MS , and ambient MS approaches , in which the accuracy and precision variations are expected to be below 20%.…”
Section: Resultssupporting
confidence: 93%
“…Bernardo et al recently reported the use of probe ESI (PESI) needles coated with molecular imprinted polymers and polypyrrole for the determination of phorbol esters (PEs) on Jatropha curcas extract (a material with a high potential for application in animal feed, yet not used because of the toxicity of PE) 38 . When compared with traditional PESI and the nonimprinted polymer, the SPME‐like probes excelled, 39 and LOQ of 920 ng mL −1 were reported with both devices for phorbol 12,13‐diacetate.…”
Section: Other Techniques For Spme Direct Coupling To Msmentioning
confidence: 99%
“…These nanomaterials possess large surface areas, specific interactions, and high adsorption capacities, which enable the selective extraction of the analytes of interest from complex matrices . In addition, the cost-effective synthetic methods allow these sorbents coated on solid substrates, such as wooden tips, stainless steel, and tungsten wire, to expand the application of AIMS. , Among various nanomaterial based adsorbents, molecularly imprinted polymers (MIPs) draw special interest due to their well-known high selectivity. , Magnetic solid-phase extraction (MSPE) has high extraction efficiency compared to other types of SPE techniques. The sorbents were directly dispersed into the liquid sample or extract, which afforded rapid extraction of analytes in MSPE.…”
Section: Introductionmentioning
confidence: 99%